Morphological diversity of the leaves and occurrence forecast of similar forms in natural hazel plantings - S. G. Biganova; Y. I. Sukhorukikh; E. K. Pchikhachev; T. A. Isuscheva (Новые технологии)
The morphological diversity of quantitative (length, width) and qualitative features (shape, degree of dissection, tip and base shape, surface character, color) of common hazel leaves growing in natural conditions of the North-West Caucasus at the altitudes of 250-1500 m A S L have been investigated. Leaf selection has been done randomly, one at a time from a plant. A total of 954 leaves have been selected in the population. The classification has been carried out according to the method used in dendrology. The scale of occurrence is based on the opinions of three experts. The forecast of the possible availability of forms has been carried out according to the law of parallelism. Statistical data processing has been performed using «Stadia» and «Microsoft Excel» computer programs. In the natural stands of hazel a significant morphological diversity of leaves in length, width, apex shape, surface (relative entropy 0.81-0.86) has been revealed. An average degree of diversity is observed in the form, dissection, base and color (relative entropy 0.54-0.64) of limbs. A very frequent occurrence (25% or more) of forms with leaves of weak and moderate degree of dissection, pointed and shortly pointed tip, heart-shaped base, with rough and smooth surface, green and light green color, medium length and width, oval and backward shape has been predicted in the population. A rare representativeness (0.99 % or less) of individuals with leaves with a rounded base, of purple or dark red color, with narrow or long plates has been assumed. The occurrence of the remaining ramets is predicted in the interval of often - not often (1-24.9 %).